Activities of daily living in chronic kidney disease patients undergoing hemodialysis at RSUD Subang - Saroni , Achmad; Rosiah, Rosiah; Minanton, Minanton (Program Studi Keperawatan, Politeknik Negeri Subang, 2023)
Background: Chronic Kidney Disease (CKD) is a kidney disease that is progressive and irreversible and can develop into end-stage renal disease (ESRD) until kidney replacement therapy is needed, one of which is hemodialysis. The condition of CKD patients who undergo hemodialysis will affect the fulfillment of needs, one of which is activities of daily living (ADLs). Purpose: to determine the picture of ADLs in CKD patients undergoing hemodialysis at RSUD Subang. Methods: This research used a quantitative study with a descriptive research design. The sample in this study consisted of 57 respondents using purposive sampling. Activities of daily living data were collected through the Katz index questionnaire and presented using frequency distribution and percentage. Results: The results showed that 49.1% of CKD patients were able to perform ADLs independently, while 50.9% of CKD patients required assistance to perform ADLs, with the range of dependence from lowest (minimal assistance), low, medium, high, very high, and very high (all assisted). Conclusion: The activities of daily living (ADLs) in patients undergoing hemodialysis tend to require assistance to do one's basic physical needs. The inability to perform ADLs may lead to unsafe conditions and poor quality of life. Nurses should be aware of the need to assess ADL in patients to help ensure that patients who require assistance are identified.